Village of the damned [videorecording (Blu-Ray)] - Reeve, Christopher; Alley, Kirstie; Hamill, Mark; Kozlowski, Linda; Paré, Michael; Salenger, Meredith; Himmelstein, David (Scream Factory, 2016)
After an unseen force invades a quiet coastal town, ten women mysteriously find themselves pregnant. Local physician Dr. Alan Chaffee and government scientist Dr. Susan Verner join forces when the women simultaneously give birth and the reign of terror begins.